Short-term Outcomes of Water Vapor Therapy (Rezūm) for BPH/LUTS in the First Czech Cohort - Wasserbauer, Roman; Pacik, Dalibor; Varga, Gabriel; Vit, Vitezslav; Jarkovsky, Jiri; Fedorko, Michal (Urology journal, 2021)
PURPOSE: To evaluate the short-term results of water vapor therapy (Rezūm) for BPH/LUTS in the first cohort of Czech patients. MATERIALS AND METHODS: Patients with BPH and moderate to severe LUTS (N = 76) who underwent Rezūm treatment from December 2019 to July 2020 were included in the prospective study. Prior to the procedure, they completed the IPSS and OABv8 questionnaires and underwent uroflowmetry, transrectal ultrasound of the prostate, and PSA sampling. The parameters before and 3 months after the procedure were compared and statistically evaluated. RESULTS: The study protocol was completed by 92% of patients (N = 70). We observed a significant increase in Qmax (median 17.7 vs. 8.8 mL/s, P < .001), Qave (9 vs. 4.5 mL/s, P = .001) and voided volume (241 vs. 171 mL, P < .001) and a significant reduction in post-void residual (average 17.5 vs. 67.7 mL), prostate volume (39.3 vs. 62.3 mL) and total PSA (median 1.9 vs. 2.5 ng/mL, resp. P values < .001). There was also a significant decrease in OABv8 score (average 7.6 vs. 16.6, P < .001) and IPSS QoL (1.6 vs. 4.0, P = .037). The improvement in the IPSS score was apparent, yet statistically insignificant (6.8 vs. 16, P = .079). CONCLUSION: Water vapor therapy is an effective and safe method of BPH/LUTS treatment in the short-term.
Keywords: výsledek terapie; hyperplazie prostaty; mužské pohlaví; Prostatic Hyperplasia; symptomy dolních močových cest; pára; Treatment Outcome; Humans; prospektivní studie; Prospective Studies; Quality of Life; Czech Republic; Steam; kvalita života; Lower Urinary Tract Symptoms; lidé; Male; Česká republika